Law and Marx’s Copernican Revolution (Notes towards a scientific System of Law after "El orden de El capital", by Carlos Fernández Liria and Luis Alegre Zahonero) - Villacañas de Castro, Luis S. (Logos. Anales del Seminario de Metafísica, 2012)
Taking for granted that Marx’s economic theory enjoys a scientific status and, furthermore, that it installed a real Copernican revolution in sociology, the present paper explores the possibility of deriving a system of law deserving the name of “scientific” in so far as it would be in keeping with the theses of the latter scientific theory. In this context, the paper argues against a claim recently sustained by Fernández Liria and Alegre Zahonero, for whom a system of right compatible with Marx’s theory would be compatible, too, with the classic juridical formulations conceived during the Enlightenment. The main reason why this paper testifies against such compatibility is that the enlightened concepts of “equality”, “liberty” and “autonomy” count with the individual as the realm for their juridical application. However, Marx’s subject matter being the social means of production (and not the individuals’ production of value), we conclude that the only juridical subject that could justifiably be derived from his economic investigation would be the “social class”. Finally, the paper suggests that the only way a scientific system of law could grant a juridical status to the individual would be by taking into account the other theory that also installed a Copernican revolution in the social sciences, though this time in the field of psychology: Freud’s psychoanalysis. Key words: Copernican revolution, science, scientific